APLIKASI FIPRONIL SEBAGAI INSEKTISIDA DAN ZPT PADA TANAMAN KACANG HIJAU (Vigna radiate. L) - Wowu, Hironimus Dongu; Agastya, I Made Indra; Marwoto, Marwoto (Universitas Tribhuwana Tunggadewi, 2021)
The purpose of this study was to determine the effect of spraying the insecticide fipronil on the growth and intensity of pest attacks on green bean plants. This study used a randomized block design with four replications. The treatments tested in this study used application of the insecticide fipronil with a concentration of 2 ml/l in the vegetative and generative growth phases, the application of insecticides on vegetative growth only, the application of insecticides on generative growth only, and control without insecticide treatment. The results showed that the insecticide fipronil used on vegetative and generative phases was used once and two times a week could reduce the intensity of leaf pests (24.98%) and pod pests (4.50%). Fipronil insecticide can also act in a plant growth substance as shown in the parameters of plant height, the number of leaves and components of mung bean seed yield is better than the control without fipronil application the application of insecticides on vegetative growth. The application of insecticides on the vegetative and generative growth phase by spraying insecticide once a week also affected yield components of 400.31g/clump and seed weight per mung bean plant of 27.67g/clump compared to other treatments.